Исследование реакции восстановления арендиазоний тозилатов - Морозова М. А. Мария Александровна; Трусова М. Е. Марина Евгеньевна; Максимчук И. О. Ирина Олеговна; Филимонов В. Д. Виктор Дмитриевич (2014, 2014)
Заглавие с экрана